Surat Janji Dan Mufakat 4 Desember 1685:Bukti Peran Voc Dalam Memelihara Perdamaian Cirebon - Tendi Tendi (IAIN Syekh Nurjati Cirebon, 2021)
Abstract : After the leadership of Pangeran Rasmi (Panembahan Ratu II), Cirebon was led by Ratu Katiga Sanak (Three Kings of Brothers). Even though they were counted as relatives, the three of them often got involved in conflicts that left Cirebon on the verge of collapse. One of the parties that helped cool the conflict and were able to reconcile the three Cirebon princes was the VOC Supreme Government through its authorized officials. However, the role of the Company was not discussed much in Cirebon's history because they were regarded as foreign parties who were suspected of being the party that had indeed driven the conflict between the Three Kings of Cirebon. This study aims to describe the Agreement of 4 December 1685 and reveal the role of the VOC in maintaining relations between the three princes who were the rulers of Cirebon. The method used in this study is the historical method, which is a series of study stages starting with the heuristic, criticism, interpretation, and historiography stages. Through this study, it can be concluded that the Agreement on 4 December 1685 was an agreement between the Cirebon Sultanate and the VOC which consisted of 13 agreement articles. In addition, this study also reveals that this agreement helped maintain peace and relations between the Cirebon princes because a number of articles demanded the unity of the princes for the peace of society and the sultanate.Keywords: agreement, prince, Cirebon, VOC, family conflict, peace